Nuclear Factor Kappa B, Matrix Metalloproteinase-1, p53, and Ki-67 Expressions in the Primary Tumors and the Lymph Node Metastases of Colorectal Cancer Cases. (6th April 2015) - Meteoglu, Ibrahim; Erdogdu, Ibrahim Halil; Tuncyurek, Pars; Coskun, Adil; Culhaci, Nil; Erkus, Muhan; Barutca, Sabri
Abstract : Colorectal cancer (CRC) is the third most frequent malignancy. Many factors such as NF- κ B, matrix metalloproteinase-1 (MMP-1), p53, and Ki-67 are likely to be involved in its development and progression. Lymph node metastases indicate increased tumor burden and tumor cell heterogeneity and affect both the treatment strategies and the prognosis. In this study, expressions of NF- κ B, MMP-1, p53, and Ki-67 were between the primary tumors and lymph node metastases in 110 Dukes' stage C, CRC cases by immunohistochemical methods, related to patients' clinical outcomes. NF- κ B, p53, and Ki-67 expressions were significantly higher in the metastatic lymph nodes compared to the primary tumor tissues (P = 0.04, P = 0.04, and P = 0.01, resp.). In the metastatic lymph nodes NF- κ B expression was correlated with both p53 (r = 0.546, P = 0.003 ) and Ki-67 (r = 0.586, P = 0.0001 ) expressions. The univariant and multivariant analyses showed that only "pT stage" preserved an independent prognostic significance for recurrence-free survival rates and 5-year overall survival rates (P < 0.001 for both). Metastatic cells can acquire different biological characteristics compared to their primaries. Elucidation of properties acquired by metastatic cells is important in order to better determine prognosis, reverse drug resistance, and discover new treatment alternatives.